On Turbulent Features of E × B Plasma Motion in the Auroral Topside Ionosphere: Some Results from CSES-01 Satellite - Giuseppe Consolini; Virgilio Quattrociocchi; Simone Benella; Paola De Michelis; Tommaso Alberti; Mirko Piersanti; Maria Federica Marcucci (Remote Sensing, 2022)
The recent Chinese Seismo-Electromagnetic Satellite (CSES-01) provides a good opportunity to investigate some features of plasma properties and its motion in the topside ionosphere. Using simultaneous measurements from the electric field detector and the magnetometers onboard CSES-01, we investigate some properties of the plasma E × B drift velocity for a case study during a crossing of the Southern auroral region in the topside ionosphere. In detail, we analyze the spectral and scaling features of the plasma drift velocity and provide evidence of the turbulent character of the E × B drift. Our results provide an evidence of the occurrence of 2D E × B intermittent convective turbulence for the plasma motion in the topside ionospheric F2 auroral region at scales from tens of meters to tens of kilometers. The intermittent character of the observed turbulence suggests that the macro-scale intermittent structure is isomorphic with a quasi-1D fractal structure, as happens, for example, in the case of a filamentary or thin-tube-like structure. Furthermore, in the analyzed range of scales we found that both magnetohydrodynamic and kinetic processes may affect the plasma dynamics at spatial scales below 2 km. The results are discussed and compared with previous results reported in the literature.